Small town revitalization issues on the example of Międzyrzecz - Kononowicz, Wanda; Pisera, Ilona (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
The article presents a method of revitalisation of the Old Town together with the castle and grange complex in Międzyrzecz, applied in a master’s dissertation prepared at the Chair of Architecture and Urban Planning of Uni versity of Zielona Góra in 2016, that received an honourable mention in the Prof. Jan Zachwatowicz international conservation competition organised by PKN ICOMOS. The revitalisation method envisaged restoration of the general spatial characteristics of a historical urban scheme, permitting diversity of the supporting components being subordinated to the overall composition. The notion of diversity applies to the buildings protected by the monuments conservator as well as to the new ones harmonising with the existing environment and to reconstructions. The eastern frontage and part of the southern frontage of the market place were destroyed by World War II and never rebuilt. Their place, as well as that of the adjacent dwelling quarters were taken by greenery. Majority of residents, especially the young ones accept this status quo. The master’s dissertation is an example of a comprehensive conservation study, from urban to architectural scale, preceded by historical-urban studies and relevant analyses of the existing state in many aspects. Results of the analyses enabled to formulate conclusions and conservation guidelines which served as the basis for the revitalisation design. The revitalisation included, amongst other things, rebuilding of the missing city blocks, preparation of a new fl oor design for the Market Place, revival of the grange complex buildings with new features and designing a landscape park to be situated on the adjacent, degraded land.